Strategies to Strengthen Pancasila Student Profile Character at Darul Mustafa Elementary School - Dhitami Dhitami; Syarbaini Saleh (Journal of General Education and Humanities, 2025)
The declining cooperation spirit among students is a significant concern in the effort to shape the character of the younger generation. Character education, particularly through the Pancasila Student Profile Strengthening Program, is crucial to instill Pancasila values from an early age. This study aims to explore the character-strengthening strategy of the Pancasila Student Profile at Darul Mustafa Elementary School, Medan, focusing on implementing the value of cooperation. Using a case study approach, this qualitative research used in-depth interviews, observation, and documentation studies as data collection techniques. The results show that Darul Mustafa Elementary School implements a holistic and integrated strategy. The values of the Pancasila Student Profile, including cooperation, independence, critical thinking, creativity, global diversity, and faith and piety, are implemented through integration in teaching and learning activities in every subject and school cultural habits (e.g., class duty, deliberation, appreciation). Outside the classroom, the application of these values is reinforced through routine activities such as "Clean Saturday" and congregational worship. Teachers act as facilitators and role models, guiding students in collaboration and conflict resolution. The school supports teachers through ongoing training and has policies encouraging the creative integration of cooperative values. Key challenges include curriculum density, student diversity, consistent value instillation, and support from home. Despite this, the school continues to strive through forums to share good practices among teachers and other adaptive strategies.